Construyendo resiliencia: Índice de vulnerabilidad del sector salud en Bolivia - Alethea Gabriela Candia; Iván Egido; Marcelo Olivera-Villarroel (Institute for Advanced Development Studies (INESAD), 2020)
– The COVID-19, by putting pressure on different edges of social structure, is emphatically showing, at the municipal level, economic distribution inequalities as well as health infrastructure precariousness. This poor distribution of resources amplifies the vulnerability of municipalities to this threat of health pandemic. In this regard, we seek to identify the Bolivian municipalities that present the highest rates of health vulnerability (IVS). The IVS distinguishes three main components: 1) hospital coverage, which measures the capacity level of the health system - personnel and infrastructure -; 2) health demand, which measures the pressure that population puts on their health systems; 3) government budget, which measures the budget that municipal governments have for facing the crisis. In addition, we propose an Index of Threats and Risks (IAR) to analyze municipalities with COVID-19 cases; characterizing their degree of risk to identify mitigation measures and, then, to help municipalities to strengthen their levels of health resilience. For this purpose, we use the Shapley decomposition technique as the main analysis method, which help us build the aforementioned indices.
Keywords: C43; H51; I18; I19; 330; COVID-19; hospital coverage; vulnerability; resilience; Bolivia